The Study of Electric Quadrupole Transition (E2) in 56Ba and 62Sm Nuclei - Jassim, F.A.; Dakhil, Z. A.; Jaber, Y.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Transition strengths ↓ 2 . u . w 2) M(E for gamma transition from first excited 21 + states to the ground states that produced by pure electric quadrupole emission in even –even isotopes of 56Ba and 62Sm have been studied through half- lives time for 21 + excited states with the intensities of γ0- transitions measurements and calculated as a function of neutron number (N). The results thus obtained have shown that; the nuclides with magic neutron number such as 56Ba 138 and 62Sm 144 have minimum value for ↓ 2 . u . w 2) M(E .